Cost-effectiveness analysis of romosozumab for severe postmenopausal osteoporosis at very high risk of fracture in Mexico. - Juan Pablo Diaz Martinez; Therese Aubry de Maraumont; Elly Natty Sánchez; Luis Miguel Camacho Cordero; Eric Yeh (PLoS ONE)
Introduction This study aims to assess the cost effectiveness of romosozumab versus teriparatide, both sequenced to denosumab, for the treatment of severe postmenopausal osteoporosis at very high risk of fractures in Mexican women. Methods A Markov model was used to assess the relative cost effectiveness of 1 year of romosozumab versus 2 years of teriparatide, both sequenced to denosumab for a total treatment duration of 5 years. Outcomes for a cohort of women with a mean age of 74 years, a T-score ≤-2.5 and a previous fragility fracture were simulated over a lifetime horizon. The analysis was conducted from the perspective of the Mexican healthcare system and used a discount rate of 5% per annum. To inform relative fracture incidence, the bone mineral density (BMD) advantage of romosozumab over teriparatide was translated into relative risks of fracture, using relationships provided by a meta-regression of osteoporosis therapy trials. Outcomes were assessed in terms of lifetime costs (2023 Mexican pesos), quality-adjusted life years (QALYs) and life-years gained (LYs). Results Base case results showed that, compared with teriparatide/ denosumab, romosozumab/ denosumab reduced costs by $51,363 MXN per patient and yielded 0.03 additional QALYs and 0.01 LYs. Scenario analyses and probabilistic sensitivity analyses confirmed that results are robust to uncertainty in model assumptions and inputs. Conclusions Results show that romosozumab/ denosumab produces greater health benefits at a lower total cost than teriparatide/ denosumab.